2022
DOI: 10.14309/ctg.0000000000000541
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Fecal Short Chain Fatty Acids With Colonic Transit, Fecal Bile Acid, and Food Intake in Irritable Bowel Syndrome

Abstract: INTRODUCTION: Short-chain fatty acids (SCFAs) correlate with colonic transit time (CTT) and may influence irritable bowel syndrome (IBS) pathophysiology. However, the clinical significance of fecal SCFAs, relationships between SCFAs and other metabolites (bile acids [BAs]), and real-time diet effects on SCFAs in IBS are uncertain. The aim was to evaluate fecal SCFA associations with IBS phenotype and mechanisms and explore effects of real-time diet. METHODS: We conducted a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Previous findings [14,15] have reported that the relief of constipation altered the composition of colonic microbiota and increased intestinal SCFA levels. Mohammed et al [16] reported that fecal SCFA levels are correlated with colonic transit. However, the patients were not diagnosed with STC and some studies included patients who had irritable bowel syndrome with diarrhea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous findings [14,15] have reported that the relief of constipation altered the composition of colonic microbiota and increased intestinal SCFA levels. Mohammed et al [16] reported that fecal SCFA levels are correlated with colonic transit. However, the patients were not diagnosed with STC and some studies included patients who had irritable bowel syndrome with diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…SCFA levels were lower in STC subjects than in healthy subjects, but the difference was not statistically significant (475.85 ± 251.68 µg/ ml vs. 639.77 ± 213.97 µg/ml, P = 0.056). Compared to healthy subjects, STC subjects had lower fecal levels of acetic and propionic acids (149.06 ± 88.54 µg/ml vs. 261.33 ± 109.75 µg/ml and100.60 ± 60.62 µg/ml vs. 157.34 ± 66.37 µg/ml, respectively, P < 0.05) and higher levels of isobutyric and isovaleric acids (27.21 ± 15.06 µg/ ml vs. 18.16 ± 8.65 µg/ml and 31.78 ± 18.81 µg/ml vs. 16.90 ± 10.05 µg/ml, P < 0.05; Fig. 1b).…”
Section: Comparison Of Scfa Levels In Fecal Supernatant Between the T...mentioning
confidence: 92%
“…We have previously shown that transit and BAM correlate with SCFA excretion in IBS. 27 Others have reported that microbiome associations with transit are largely influenced by altered bile acid biotransformation. 19 In this current study, several bacterial species with fermentative capacity or varied substrate processing functions correlated with total stool SCFA, but not with transit or bile acids.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, studies 10,15,24 that have assessed stool SCFA in distinct IBS subgroups have reported more consistent associations of stool SCFA with IBS subtypes as well as correlations of stool SCFA with measurable IBS traits such as colonic transit, bowel functions, and bile acid excretion. [24][25][26][27] Despite these reports, the intercorrelation between SCFA, bile acids, and transit time complicates the assessment of whether microbial composition is directly responsible for SCFA profiles or if relationships between the intestinal microbiome and excreted SCFA is clinically valuable due to the complex and dynamic nature of the microbial ecosystem. However, recent work 28 has suggested that individual taxa, rather than complex ecological communities, could drive changes in SCFA output in response to dietary fiber.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, increasing stress hormones such as corticosteroids and catecholamines induced by exercise can negatively affect gut motility, microbiota, and SCF production and reduce GI transport activity [66]. Thus, decreasing SCF can result in dysregulation of visceral sensation and associate with constipation and IBS symptoms [67].…”
Section: Do Physical Exercises Impact Irritable Bowel Syndrome and How?mentioning
confidence: 99%